The SpacePy space science package at 12 years - Niehof, Jonathan T.; Morley, Steven K.; Welling, Daniel T.; Larsen, Brian A. (Frontiers in Astronomy and Space Sciences, 2022)
For over a decade, the SpacePy project has contributed open-source solutions for the production and analysis of heliophysics data and simulation results. Here we review SpacePy’s design principles and functionality, before examining recent advances and the future of SpacePy in the broader scientific Python ecosystem. We conclude with some of the work that has used SpacePy.